1987
DOI: 10.1007/bf00538197
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the macrophage mannose-6-phosphate receptor in the recognition of Leishmania mexicana amazonensis

Abstract: Significant differences were found in the ability of resident mouse peritoneal macrophages to ingest amastigote and promastigote forms of Leishmania mexicana amazonensis. Differences in the association index of the parasites to the macrophages were also found between infective and non-infective promastigotes. Evidence was obtained suggesting that the macrophage receptor, which recognizes mannose-6-phosphate-containing units found in lysosomal enzymes, is involved in the association with the macrophage of proma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
2
9
0
2
Order By: Relevance
“…There is some evidence in the literature that may help to explain these differences. First, it has been shown that different parasite surface molecules and macrophage receptors are involved in the initial cell-recognition process (Saraiva et al 1987;Russell et al 1992;Mosser and Rosenthal 1993). Second, it was observed that PVs containing infective promastigotes do not fuse efficiently with endosomes (Desjardins and Descouteaux 1997), whereas extensive fusion occurs with PVs containing amastigotes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is some evidence in the literature that may help to explain these differences. First, it has been shown that different parasite surface molecules and macrophage receptors are involved in the initial cell-recognition process (Saraiva et al 1987;Russell et al 1992;Mosser and Rosenthal 1993). Second, it was observed that PVs containing infective promastigotes do not fuse efficiently with endosomes (Desjardins and Descouteaux 1997), whereas extensive fusion occurs with PVs containing amastigotes.…”
Section: Discussionmentioning
confidence: 97%
“…Microscopic studies have demonstrated differences in the early ultrastructural phagocytic events of both Leishmania forms by macrophages (Strauss et al 1993). The amastigote phagocytic rate by macrophages is greater (Alexander and Vickerman 1975;Saraiva et al 1987) and it was also observed that NAD(P)H activity was greater in PVs containing promastigotes (Pimenta and De Souza 1988). However, biochemical studies carried out in the isolated PV, which may help to clarify the mechanisms involved in its biogenesis, are almost absent.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, binding of L. monocytogenes to McCoy cells was significantly inhibited by M6P in a dose-dependent manner. Competitive inhibition studies using soluble M6P as an inhibitor of binding of other ligands are established techniques for the investigation of IGFIIR function (37,62,73). The M6P effects were specific, because G6P, a closely related analogue that does not bind to the IGFIIR (38), had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Promastigotes labeled with PKH26 showed a strong and uniform staining pattern (C, D); early interaction with macrophages for 15 min revealed partial staining of adherent promastigotes (arrows, G, H), and later the diusion of a probe through a macrophage was observed, with adherent (arrowheads) and intravacuolar (arrows) parasites being slightly stained, after 60 min of interaction (K, L). (v Parasitophorous vacuole) Bars 10 lm to a large extent (Saraiva et al 1987) via cup-shaped extensions, whereas ingestion of promastigotes takes place via long and prominent surface projections (Strauss et al 1993), which would explain the clearer labeling of the contact area in the case of promastigotes. Later the intravacuolar parasites were labeled, indicating transfer of the host's membrane lipophilic molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Both promastigote and amastigote have to attach to the phagocyte surface before they are taken in (Mosser and Rosenthal 1993). Internalization occurs via a conventional phagocytic process mediated by macrophage receptors, and several surface receptor-ligand systems have been shown to participate in the recognition process (Chang 1983;Saraiva et al 1987;Puentes et al 1988;Soteriadou et al 1992). Depending on the Leishmania form involved, the protozoan surface composition may select dierent receptor sites (Saraiva et al 1987) on the phagocytic cell membrane, modifying the PV membrane composition, mainly during the initial phagocytic stages, where the PV is formed by part of the plasma membrane, to which the parasite has adhered.…”
Section: Introductionmentioning
confidence: 99%